Construction and use of GFP and DsRed expressing vectors and transformation in Borrelia afzelii - Honeder, Sophie (Jihočeská univerzita, 2017)
The aim of this thesis was to create a GFP containing Borrelia shuttle vector and DsRed expressing strains of a European Borrelia species, Borrelia afzelii to further our understanding of the complex interactions of this European Lyme Disease pathogen with its hosts: ticks and mammals.
Construction and use of GFP and DsRed expressing vectors and transformation in Borrelia afzelii
Keywords: Borrelia; fluorescence; gfp; lyme disease; genetic tools and manipulation; genetic tools for visualization; transformation; shuttle vector; Borrelia; fluorescence; gfp; lyme disease; genetic tools and manipulation; genetic tools for visualization; transformation; shuttle vector